Studying local government's performance of Taft, Eastern Samar - Aserit, Evangeline C. (2007)
In view of the recent interest of many sectors to assess how various entities contribute to the promotion of public interest, the formulation of indicators of governance both timely and appropriate. This research is thus an attempt to take this effort a step further by focusing on the Minimum Basic Needs approach and how MBN indicators can enhance the assessment of governance (Bautista, 2002, 124).